Role of formal and informal nonprofit leadership in rural development - Oto Potluka; Petr Fanta (University of Basel, Center for Philanthropy Studies (CEPS), 2018)
Background: Place-based leadership plays a crucial role in local development. However, the role of nonprofit leaders is still an under-researched topic. Thus, we ask whether nonprofit leadership helps to develop rural areas and makes them attractive. Data and methodology: On a sample of 6,262 Czech municipalities, we tested whether membership of municipalities in local action groups (LAGs) and nonprofit leadership attributed to population growth. We have applied the propensity score method combined with the differences-in-differences approach. Results: Our analysis has not proved the effects of LAGs on the attractiveness of municipalities, but for the participation of nonprofit leaders. The estimate for effects of being in a LAG is negative and insignificant (- 1.071% change of population when a municipality is a member in a LAG, p-value=0.151), while for share of nonprofit leaders in LAGs, the estimates are positive and significant (+9.239% change relating to an increase of 1% share of NPOs in LAGs). Conclusions: These results underline the importance of bottom-up approaches with voluntary engagement. Moreover, they demonstrate negative aspects of top-down imposed public policies.
Keywords: 330; Local action groups; Rural development; Nonprofit leadership; Nonprofit organizations; Place-based leadership; Co-creation